PERGESERAN PERAN KYAI DALAM POLITIK DI BANTEN ERA ORDE BARU DAN REFORMASI - ABDUL HAMID (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2011)
Kyai is one of traditional leaders in Banten. The political role of kyai in Banten has risen and fell. From collonial collapsed to Indonesian Revolt 1945, the leadership of kyai had increased in the peak performance. In 1945 until 1950, all of the Bupati in Banten were positioned by kyai. Since that time to now, in all of dimensions, the leadership of kyai has decreased. In New Order era, many kyais were organized as supported organization of ruling party. It was mutualism relation, ruling party got mass supports and kyai got material support for himself and pesantren. Impad of this strategy was increasing of charisma, influence, and trust. On the other hand, some kyais got oppression because of their independences and critics to government. In reformasi era, kyai had been fragmented in many political powers, but still as supporting actor not as the main one. To fulfill their needs, both for their selves and for pesantren, some kyais has done pragmatically and depended on others. This met with politician or government purposes to get religious legitimacy. The mix of political and economic weakness made kyai failed to made reformasi era as an opportunity to get back their ultimate role in politics. Keywords: Kyai, Political Role, New Order, Reformation Era, Banten.